Integrasi Pasar Cabai Rawit Di Kabupaten Kutai Kartanegara - Bahari Joko Susilo; Arista Damayanti; Astik Drianti (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2023)
One of the main measures of marketing efficiency is market integration, which contributes to the formation of agricultural policy. Thus, it is important to understand how much changes in consumer prices can impact farmers in order to increase the effectiveness of policies and price control measures. The purpose of this research is to look at the integration of cayenne pepper prices in the Mangkurawang and Loa Kulu markets using the correlation coefficient R. Data from ten traders in each market were collected for 30 days. The results showed that although there was a positive relationship between the price of cayenne pepper in the Mangkurawang and Loa Kulu markets, the correlation coefficient was moderate, namely 0.49. In addition, price margins in the Mangkurawang and Loa Kulu markets tended to be stable during the study. This shows that changes in the price of cayenne pepper were relatively stable over that time period. Although there is a correlation between the price of cayenne pepper in the two markets, the correlation is not strong. The price of cayenne pepper in both markets is still integrated, although not fully, because the price relationship is not strong; however, differences in competition in the Mangkurawang and Loa Kulu markets can affect the level of price parity, while differences in transportation costs can affect price margins.